2020
DOI: 10.1002/cam4.3320
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of localized prostate cancer in younger men aged ≤ 50 years treated with radical prostatectomy in the PSA era: A systematic review and meta‐analysis

Abstract: Objectives With the rapid increase in younger age prostate cancer (PCa) patients, the impact of younger age on decision‐making for PCa treatment needs to be revaluated in the new era. Materials and Methods A systematic literature search was performed using PubMed, EMBASE, and Web of Science up to October 2019 to identify the eligible radical prostatectomy (RP) studies focusing on understanding the impact of age on clinicopathological features and oncological prognosis in patients with localized PCa in PSA era.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
(124 reference statements)
0
6
0
7
Order By: Relevance
“…Age is, although a social construct, has biological implications. The clinicopathological feature of PCa in middle age is more favorable and offers higher survival 35 . Hypothetically, persons above the mid‐age are at higher risk of biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Age is, although a social construct, has biological implications. The clinicopathological feature of PCa in middle age is more favorable and offers higher survival 35 . Hypothetically, persons above the mid‐age are at higher risk of biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed survival time of patients is affected by many factors, such as age, ethnicity, genetic factors etc. [10,11]. In addition to tumor factors, age is one of the most important factors that has great effects on the prognosis of men with mPCa [10].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…PCa is very rare among young patients and might be more aggressive in terms of biological behavior. Zheng et al [11] reported that younger patients were associated with significantly worse outcomes in high-risk group patients. For young patients with mPCa, the detailed survival outcomes remain inconclusive.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…El punto de cohorte de la edad no está establecido, pero se considera de inicio temprano si el paciente es menor de 50 años, sin embargo otros estudios lo han establecido en menores de 60, 55 y 45 años de edad. (11) En Estados Unidos en el año 2012 cerca del 10% de los hombres con CP (241 740 personas) fueron diagnosticados antes de los 55 años. (12) En un estudio realizado con los datos obtenidos de SEER (The Surveillance, Epidemiology, and End Results) que incluyó el análisis de 30 338 pacientes con CP durante 1998 y 2003, determinó que el 9% eran pacientes ≤55 años.…”
Section: Cáncer De Próstata De Inicio Tempranounclassified
“…(1.09-1.74)), (11) en este análisis se incluyeron tres estudios. (19)(20)(21) Sin embargo, en los jóvenes con CP de alto riesgo se observó asociación con peores desenlaces oncológicos.…”
Section: Cáncer De Próstata De Inicio Tempranounclassified